1971
DOI: 10.1210/jcem-33-1-63
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Total Thyroxine and Absolute Free Thyroxine and the Influence of Absolute Free Thyroxine on Thyroxine Disposal in Humans1

Abstract: Studies were conducted concerning the relation between TT< and AFT 4 in a family with TBG deficiency, consisting of 8 affected and 16 unaffected members, and in a group of 48 normals. A highly significant positive relationship between these 2 parameters was found within the family, as well as within the group of normals. Subjects with TBG deficiency had low TT 4 and lowered AFT4 levels. From additional studies it appeared that there existed no relationship between AFT 4 and T 4 disposal in 20 euthyroid control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…In all, the PFT4 was increased. Values for the AFT4I fell at the lower end of the normal range in all four patients, a finding similar to that reported by Hennemann, Beckers, Docter, Dolman, and De Nayer (19). A pronounced increase in total Tc-clearance rate was also observed, values ranging between 2.5 and five times those expected on the basis of age and weight.…”
Section: Discussionsupporting
confidence: 89%
“…In all, the PFT4 was increased. Values for the AFT4I fell at the lower end of the normal range in all four patients, a finding similar to that reported by Hennemann, Beckers, Docter, Dolman, and De Nayer (19). A pronounced increase in total Tc-clearance rate was also observed, values ranging between 2.5 and five times those expected on the basis of age and weight.…”
Section: Discussionsupporting
confidence: 89%
“…FT4, determined in all three families, proved to be normal or slightly reduced, as also reported by others (1,2,3,8,10) in persons with TBG deficiency.…”
Section: Discussionsupporting
confidence: 88%
“…We have previously analyzed published data on 24 families from which it was concluded that although only in one-third of the families was X-chromosome-linked transmission suggested by the authors, the remaining kindreds showed no evidence of incompatibility with such mode of inheritance (3). With a single exception (12), a similar conclusion can be drawn from the analyses of 10 pedigrees with TBG abnormalities published since our previous review (7,8,12,(28)(29)(30)(31)(32)(33) and from the two new families presented. The family in question included an XX female, brother, and son with undetectable serum TBG, reduced TBG in a daughter, and normal TBG in the parents (12).…”
Section: Clinical Materialssupporting
confidence: 67%
“…The observed changes in T4 kinetics seem to be related to changes in the fractional turnover rate and/or the extrathyroidal T4 pool associated with the increased or decreased total T4-binding capacity of TBG in serum (5). Though some reports have indicated that the free T4 concentration may be altered in the serum of subj ects with changes in the T4 capacity of TBG (6)(7)(8), the bulk of evidence and the hormone kinetic studies suggest that the free T4 level in serum remains within the normal range and that it determines the thyroid hormone-dependent metabolic status of the subjects.…”
Section: Introductionmentioning
confidence: 99%